Game Hago Sebagai Media Pembelajaran di Sekolah Dasar - Kurnia, Ita; Noviantiningtyas , Tera; Nur Rohmania , Qonita (JURNAL PENDIDIKAN DASAR NUSANTARA, 2021)
Abstract: Indonesia is currently facing an industrial revolution 4.0. This affects the education era which is characterized by the use of digital technology in the learning process. The use of technology-based learning media is absolutely necessary in the learning process, Hago is one of them. The purpose of this study was to determine the effectiveness of how to improve student learning outcomes in Elementary Schools (SD) through online game learning media (Hago). This research took place at SDN Gogorante Kediri Regency with the research subjects were fourth grade students. In collecting data using 5 steps, namely identification of research variables, identification of research variables, research techniques and approaches, data collection techniques, question validation, and data analysis techniques. Based on the results of the trial, a minimum score of 50 and a maximum score of 90 was obtained with an average student score of 74.80 which was already above the KKM of 70.The conclusion from the trial results is that the use of learning media based on Hago online games has influence on student learning outcomes and is suitable for use as a learning medium. Keywords: hago, online game, learning media.